EFFECTS OF PROMOTION, EWOM, HEDONIC MOTIVATION ON TIKTOK SHOP IMPULSE BUYING - Eko Sasono; Endi Isnarno; Faulina Wijayanti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
This study is motivated by the increasing phenomenon of impulse buying behavior among students in line with the rapid growth of e-commerce, particularly on the TikTok Shop platform. Such behavior is influenced by stimuli including sales promotion, electronic word of mouth (eWOM), and hedonic shopping motivation. This study aims to analyze the effects of these three variables on impulse buying among students of STIE Semarang. The population consists of 122 regular morning class students from the Management and Accounting majors, cohort 2021, with a sample of 54 respondents collected through questionnaires. The analytical methods employed include validity and reliability tests, classical assumption tests, F-test, t-test, multiple linear regression, and coefficient of determination. The results indicate that sales promotion and hedonic shopping motivation have a significant effect on impulse buying, while eWOM does not have a significant effect. The coefficient of determination (R²) of 0.610 shows that 61% of the variance in impulse buying is explained by the three variables. The implications suggest that TikTok should optimize promotional strategies through discounts, cashback, and coupons, as well as create enjoyable shopping experiences through interactive features to enhance users’ impulse buying behavior